Ki Hadjar Dewantara and the Philosophy of Education - Diyoba Azhar Fuadi; Gusti Yuniarti; Nelian Nelesti; Septen Heri; Jon Carnolis; Merri Sri Hartati; Susiyanto Susiyanto (Institute of Advanced Knowledge and Science, 2025)
Education has a major role in building a strong country and producing talented citizens. However, the Indonesian education system still places too much emphasis on academic aspects rather than character and moral development. Ki Hadjar Dewantara's ideas, which emphasize building national character, remain relevant in this era of globalization. This research uses a literature study method by analyzing various literature related to Ki Hadjar Dewantara's thoughts, educational philosophy, and current educational challenges. Data was obtained from books, journals and Ki Hadjar Dewantara's writings which document his views on education and culture. The research results show that Ki Hadjar Dewantara's educational concept is based on the principle